2020
DOI: 10.1177/1069072720933556
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Managing Work and End-of-Life Care: Challenges, Rewards and Recommendations for Vocational Psychologists

Abstract: End-of-life care is a form of unpaid care work that is primarily the responsibility of women and can affect their career development, employment, finances, and vocational success. This paper provides a review of the literature on the career and economic effects of providing unpaid end-of-life care for women caregivers. Illustrative reflections from women caregivers highlight challenging and positive aspects of providing end-of-life care. Challenges identified by the women caregivers included managing conflicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For our purposes, empirical meant studies with an explicit research design where data were collected and analyzed and results were reported. Although excellent theoretical and critical contributions have been made in response to calls for understanding the experiences of women at work (e.g., Fouad & Santana, 2017; O’Brien et al, 2021), we believed that a review that focused on empirical research would allow us to focus more directly on the methods used to study the area. Case studies that were illustrative of a pre-existing theoretical paradigm rather than investigating a new phenomenon did not meet our criteria for empirical work and were subsequently excluded from the review.…”
Section: Methodsmentioning
confidence: 99%
“…For our purposes, empirical meant studies with an explicit research design where data were collected and analyzed and results were reported. Although excellent theoretical and critical contributions have been made in response to calls for understanding the experiences of women at work (e.g., Fouad & Santana, 2017; O’Brien et al, 2021), we believed that a review that focused on empirical research would allow us to focus more directly on the methods used to study the area. Case studies that were illustrative of a pre-existing theoretical paradigm rather than investigating a new phenomenon did not meet our criteria for empirical work and were subsequently excluded from the review.…”
Section: Methodsmentioning
confidence: 99%